The terrible two get worse - Barnett, Mac; John, Jory (Barnett, Mac. Terrible Two., 2016)
"Friends and pranking partners Miles and Niles face a tough challenge when their favorite goat and nemesis, Principal Barkin, is replaced by his stern, no-nonsense father, Former Principal Barkin, who turns the school into boot camp"--